Vaccine platform for prevention of tuberculosis and mother-to-child transmission of human immunodeficiency virus type 1 through breastfeeding. - Im, E; Saubi, N; Virgili, G; Sander, C; Teoh, D; Gatell, J; Mcshane, H; Joseph, J; Hanke, T (2007)
Most children in Africa receive their vaccine against tuberculosis at birth. Those infants born to human immunodeficiency virus type 1 (HIV-1)-positive mothers are at high risk of acquiring HIV-1 infection through breastfeeding in the first weeks of their lives. Thus, the development of a vaccine which would protect newborns against both of these major global killers is a logical yet highly scientifically, ethically, and practically challenging aim. Here, a recombinant lysine auxotroph of Mycobacterium bovis bacillus Calmette-Guérin (BCG), a BCG strain that is safer than those currently used and expresses an African HIV-1 clade-derived immunogen, was generated and shown to be stable and to induce durable, high-quality HIV-1-specific CD4(+)- and CD8(+)-T-cell responses. Furthermore, when the recombinant BCG vaccine was used in a priming-boosting regimen with heterologous components, the HIV-1-specific responses provided protection against surrogate virus challenge, and the recombinant BCG vaccine alone protected against aerosol challenge with M. tuberculosis. Thus, inserting an HIV-1-derived immunogen into the scheduled BCG vaccine delivered at or soon after birth may prime HIV-1-specific responses, which can be boosted by natural exposure to HIV-1 in the breast milk and/or by a heterologous vaccine such as recombinant modified vaccinia virus Ankara delivering the same immunogen, and decrease mother-to-child transmission of HIV-1 during breastfeeding.